A 2D model for coupled heat, air, and moisture transfer through porous media in contact with air channels. (April 2016) - Belleudy, Clément; Woloszyn, Monika; Chhay, Marx; Cosnier, Matthieu
Highlights: A new heat–air–moisture model applied to porous media and air channels is developed. Good agreement with numerical benchmarks from literature is obtained. Simulations based on a 2D wall assembly show strong couplings between transfers. Abstract: Detailed modelling of air leakage paths through complex building wall assemblies is a challenging task. It requires transient modelling of diffusion and advection phenomena through fluid and solid domains, including porous materials and air channels. In this article, the development of a numerical model coupling heat air and moisture transfers (commonly called HAM transfers) is presented. The model is able to deal with non-isothermal air flow through complex 2D (two-dimensional) geometries, combining air channels and porous media, air permeable or not. A stepwise 1D validation of the model is achieved with numerical benchmarks. The model is then tested on a 2D air leakage configuration subjected to infiltration and exfiltration scenarii.